A Comparative Study to Assess the Crohnâ€s Disease type using Statistical and Fuzzy Logic Methodology - Singh, Dharmpal; Sahana, Sudipta; Saddam Ahmed, SK (International Journal of Computer Sciences and Engineering, 2025)
Crohn's disease is one class inflammatory bowel disease (IBD) affect any part from mouth to anus of gastrointestinal tract. Genome based wide association studies has fruitfully identified vulnerability of loci that can be triggered by environmental factors ensuing troubling inborn or intestinal blockade. In this paper, an effort has been made to assess Crohn’s Disease survivability using data mining and soft computing technique. A comparative study among five least squares based statistical models has been done on the data set and fuzzy has been applied to improve the optimal accuracy level of the error of statistical method. It has been further observed that fuzzy logic has outperformed the least squares based statistical models with accuracy rate of 94.44%.